We are wise enough to hide: incidence of impacted tooth excluding third molars- a retrospective study - KOSHY, SAM JOHN; MADHULAXMI M; SIVAKUMAR (The journal of contemporary issues in business and government, 2020)
Tooth eruption is a process whereby the forming tooth migrates from its intraosseous location in the jaw to its functional position within the oral cavity. A variety of eruption problems arise during the transitional dentition period and one such problem is ectopic eruption. Ectopic eruption is a disturbance in the usual course of tooth eruption which may lead to impaction of the said tooth. This study sheds light to all impacted teeth in the oral cavity excluding third molar teeth. The aim of this study is to determine the frequency of impacted teeth excluding third molars that need surgical removal. This is a single centre retrospective study done from June 2019 – March 2020. Out of 786 patients who underwent surgical removal of their impacted teeth, 51 patients were considered for the study based on the inclusion criteria. The parameters examined and processed with relevance to impacted teeth were type of impaction based on tooth and its location of impaction, age and gender of patient. IBM SPSS Version 20 was used for statistical analysis. The most common tooth of impaction excluding third molar impactions was canines accounting for 51% of the total cases. There was a definitive predilection for male over females on the incidence of ectopic impactions (64.7%). The association of age of the patient and tooth of impaction revealed the incidence of canine impaction in the age group of 11-20 years and Para molar impactions in the age group of 21-30 years, which is statistically insignificant as p=0.273>0.05, by Chi square test. This study concludes to establish the predominance of canine impactions that arise in the age group of 11-20 years with gender predilection in males.